KECEMASAN TOKOH NEMUKO SENNEN DALAM KOMIK UMI YORI MO FUKAKU KARYA AKEMI YOSHIMURA TINJAUAN PSIKOLOGI SASTRA - Puspita Oktaviani, Ni Luh (Humanis, 2014)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 This thesis entitled “Anxiety Analysis of Nemuko Sennen in Umi yori mo Fukaku Comics by Akemi Yoshimura, a Review of Psychological Analysis”. Anxiety characteristic of Nemuko Sennen in the comics was analyzed along with her efforts to cope with her anxiety. Descriptive analysis and formal method were used in this research. Theory of anxiety that used in this research was adopted from Sigmund Freud (2010), while theory of semiotics was taken from Marcel Danesi (2010). Analytical research showed that Nemuko Sennen had two kinds of anxieties, such as: moral anxiety and realistic anxiety. Additionally, Nemuko Sennen did her efforts, such as: paid back her family debt to Isshiki’s family, kept away from Juzou, tried to commit suicide, fixed the thing that she broke, and tried to keep her mind away from the forecast to overcome her anxiety. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Anxiety, Character